2020
DOI: 10.1530/joe-19-0112
|View full text |Cite
|
Sign up to set email alerts
|

Neurosecretory protein GL induces fat accumulation in mice

Abstract: We recently discovered a novel gene encoding a small secretory protein, neurosecretory protein GL (NPGL), which stimulates feeding behavior in mice following acute administration. These findings suggest that dysregulation of NPGL contributes to obesity and metabolic disease. To explore this possibility, we investigated the impact of prolonged exposure to NPGL through 13 days of chronic intracerebroventricular (i.c.v.) infusion and examined feeding behavior, body composition, expressions of lipid metabolic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 37 publications
1
43
1
Order By: Relevance
“…We have demonstrated that NPGL is involved in energy homeostasis in vertebrates, including birds and rodents [1316, 26, 27]. In particular, we recently showed that Npgl overexpression modestly stimulated feeding behavior and fat accumulation in rats [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that NPGL is involved in energy homeostasis in vertebrates, including birds and rodents [1316, 26, 27]. In particular, we recently showed that Npgl overexpression modestly stimulated feeding behavior and fat accumulation in rats [14].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that chronic i.c.v. infusion of NPGL for 13 days reduced energy expenditure and locomotor activity in mice [16]. On the other hand, many studies have demonstrated that obesity resulting from fat accumulation is closely related to inflammation in the WAT [17, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…The feeding regulatory neuropeptides and lipid metabolic enzymes have been shown to display rhythmic activity, contributing to feeding and metabolic rhythms [20][21][22]27,28]. We had recently identified novel brain substances (NPGL and NPGM) in birds and rodents and demonstrated their important roles in regulating feeding behavior and fat accumulation [30,31,[33][34][35]. However, the relationship between the biological rhythm and NPGL/NPGM expression has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we discovered two novel cDNAs (viz., neurosecretory protein GL (Npgl) and its paralog neurosecretory protein GM (Npgm)) that encode the precursors of NPGL and NPGM, respectively, in chicken, rat, mouse, and human brains [29][30][31][32]. We revealed that NPGL is expressed in the mediobasal hypothalamus (MBH) of mouse and rat brains and promotes feeding and fat accumulation [30,31,33]. It is likely that NPGM has a similar biological function because both neurosecretory proteins are produced in the same neuron [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation